Tarbawi Hadith Theory In Education And Its Applications - Ahmad Hafizon; Nurhadi; Ilyas Husti (CV. AFDIFAL MAJU BERKAH, 2023)
This paper aims to explain the meaning of the theory of tarbawi hadiths in education and their application in real life, especially Islamic education. The research method in this paper uses qualitative research methods which emphasize meaning rather than generalizations. Hadith is one source of Islamic educational theory. Hadith as a form of implementing the personality of the Prophet Muhammad which have a content of educational theory that can be used as a mirror for the development of education. Besides that, this paper also explains the scope of tarbawi hadiths in which many aspects are involved, both directly and indirectly, such as; educational goals, students, educators, educational methods, educational facilities and infrastructure as well as educational evaluation, where all of them are interrelated with one another.